Работа с кадрами в университетских библиотеках СССР - Синкявичюс, Клеменсас (Knygotyra, 1976)
Personnel management in Soviet university libraries implies a wide range of questions: the estimation and planning the library staff, the rights and obligations of the management and employees; professional training of personnel including the improvement of professional skill, normalization of work and the stimulation of the initiative of each librarian.In the last decade special attention is being paid to questions of scientific organization of labour, the regulation of the place and functions of the different segments of the university library in its overall structure, the working out of personal instructions for each member of the staff.At the same time much has been achieved in the improvement of the professional skill of librarians through extra-mural and evening courses, training of librarians within the library itself and in the system of methodological guidance.Personnel management is a multi-facet pedagogical, psychological, sociological and labour problem. On the optimal solution of this problem depend not only the results of the library’s activities and the quality of library service catering to the university’s needs in books and information but also the moral satisfaction that the librarian finds in his everyday work.